Evaluation of the Nursing Student Performance Assessment Model in Integrated Clinical Practice - Darmojo, Hardjito S; Rossa, M. Adila; Fairuza, Filda (LPPM AKPER FATMAWATI, 2019)
Integrated clinical practice is an essential component of nursing education because it serves as the primary means for students to apply theoretical knowledge, clinical skills, and professional attitudes in the context of real-life healthcare. Therefore, a performance assessment model capable of evaluating student competency comprehensively, objectively, and sustainably is needed. This study aims to evaluate the nursing student performance assessment model in integrated clinical practice and analyze the influence of assessment components on student clinical performance. The study used a quantitative, descriptive-analytical design with a survey approach. The study sample consisted of 180 final-year nursing students undergoing integrated clinical practice, selected using a stratified random sampling technique. The research instrument was an integrated clinical performance assessment questionnaire covering the domains of clinical knowledge, psychomotor skills, and professional behavior. Data analysis was performed using descriptive and inferential statistics, including a difference test and multiple linear regression. The results showed that the majority of students had high clinical performance, with the highest scores in the professional behavior domain. The performance assessment model, which included rubric clarity, assessment consistency, and preceptor feedback, had a significant effect on student clinical performance. These findings confirm that structured and integrated clinical assessment serves not only as an evaluation tool but also as a learning strategy that supports the holistic development of student competencies. This study recommends the consistent implementation of an integrated clinical assessment model to improve the quality of nursing education and graduates' readiness for professional practice.